Упростите выражение и вычислите результат: (в – 5)(в – 1) – (в + 1)(в – 3) при в = -22/3.
Упростите выражение и вычислите результат: (в – 5)(в – 1) – (в + 1)(в – 3) при в = -22/3.
Ответ(ы) на вопрос:
[latex](b - 5)(b - 1) - (b + 1)(b - 3)=b^2-6b+5 - (b^2-2b-3)=b^2-6b+5 - b^2+2b+3=-4b+8[/latex] Если b=-22/3, то [latex]-4\cdot\frac{-22}{3} +8=\frac{88}{3} +8=29\frac{1}{3} +8=37\frac{1}{3} [/latex]
(в – 5)(в – 1) – (в + 1)(в – 3)=b²-b-5b+5-(b²-3b+b-3)=b²-6b+5-b²+3b-b+3=-4b+8=-4(b+2) -4(b+2) при -22\3 -4(b-2)=-4(-22\3-2)=88/3+8=29⅓ +8=37⅓ Ответ:37⅓
Не нашли ответ?
Похожие вопросы